2018
DOI: 10.1038/s41557-018-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational evidence of halogen bonds involving astatine

Abstract: The importance of halogen bonds-highly directional interactions between an electron-deficient σ-hole moiety in a halogenated compound and an acceptor such as a Lewis base-is being increasingly recognized in a wide variety of fields from biomedicinal chemistry to materials science. The heaviest halogens are known to form stronger halogen bonds, implying that if this trend continues down the periodic table, astatine should exhibit the highest halogen-bond donating ability. This may be mitigated, however, by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 60 publications
2
101
0
Order By: Relevance
“…[42,44,[48][49][50][51][52][53] For instance, the interaction energy of At-mediated XBs can be affected by SOC effects up to 35 %. Nevertheless, many studies have demonstrated that the quantum calculations should also include the relativistic spin-orbit interaction for At-containing compounds.…”
Section: Two-component Relativistic Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42,44,[48][49][50][51][52][53] For instance, the interaction energy of At-mediated XBs can be affected by SOC effects up to 35 %. Nevertheless, many studies have demonstrated that the quantum calculations should also include the relativistic spin-orbit interaction for At-containing compounds.…”
Section: Two-component Relativistic Resultsmentioning
confidence: 99%
“…The sum runs over a gaussian expansion (index k) of semi-local short-range radial potentials, which are different for different orbital angular-momentum quantum numbers l, and, for a given l, for the two total oneelectron angular-momentum quantum numbers j = l � 1 = 2 .P lj is the 2c projector onto the complete space of functions with angular symmetry l, j around the core under study. [26,44,46] The small-core pseudo-potentials ECPnMDF with n = 60, 28 and 10 were used for the At, I and Br atoms, respectively. Note that a transcription of such kind of pseudo-potentials into a scalarrelativistic spin-averaged part (averaged relativistic potential b V AREP ) and an effective one-electron spin-orbit operator ( b V SO ) is easily possible.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] The changes represent increases of 0.4 %t o1 .6 %f or 35 Cl, 2.3 % to 3.8 %f or 79/81 Br, and 2.9 %t o4 .0 %f or 127 I. Each nucleus has au nique Sternheimer antishielding factor [57,58] and quadrupole moment (Q[ 127 I] = À617 mb; Q[ 79 Br] = 308.7(2) mb); Q[ 81 Br] = 257.9(2) mb; Q[ 35 Cl] = À81.12 mb), [59] with the latter taken into account using Equation (1) and solving for V 33 .The substantial shifts in the resonance frequencies as ar esult of halogen bonding far exceed the possible variation due to temperature fluctuations.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Halogen bonding is an on-covalent interaction occurring between the area of elevated electrostatic potential associated with ar egion of depleted electron density on ah alogen (halogen-bond donor), [1,2] named the s-hole, [3][4][5] and an ucleophilic center such as aL ewis base (halogen-bond acceptor). [6] Over the last decades,halogen bonding has emerged as av ersatile non-covalent interaction for use in crystal engineering, [7,8] pharmaceuticals, [9][10][11] material sciences, [12,13] and anion receptors, [14][15][16][17] to name af ew,w ith several reviews available on the subject.…”
Section: Introductionmentioning
confidence: 99%